Bersentuhan dengan Lawan Jenis sebagai Pembatal Kesucian Saat Tawaf Perspektif Fikih Ibadah: Touching the Opposite Sex as an Invalidator of Purity During Tawaf from the Jurisprudence of Worship Perspective - Dewi Indriani; Sri Reski Wahyuni Nur; Lutfiah Dinda Amaliah Amir (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
The problems that the author raises in this study are: first, What are the views of scholars regarding touching the opposite sex as a cause of ablution invalidation; second, How is the analysis of the evidence for the occurrence of scholars' ikhtilaf in the matter of touching the opposite sex as a cause of ablution invalidation; and third, What is the status of the validity of the ablution of people who touch the opposite sex during tawaf. This study uses a qualitative research method with library research, namely by collecting data from various sources such as books and other scientific works. In this study, the approach methods used are juridical-normative, sociological and comparative/comparative approaches. The results of the study were as follows: first, when touching the opposite sex, Imam Abu Hanifah did not see that this could invalidate ablution, Imam Malik stated that if this does not invalidate ablution but if accompanied by lust then it can be invalidated whether using a cloth barrier or not, while Imam Syafii absolutely views that this invalidates ablution, and the Hanbali school of thought views that touching the opposite sex does not invalidate ablution; second, differences of opinion occur because there are two words that have different interpretations by scholars, namely لاَمَسْتُمْ and لَمَسْتُمْ which are interpreted as having intercourse and touching hands, the opinion that makes it easier in daily practice is having intercourse; third, scholars disagree about the law of ablution when performing tawaf, but when observing the conditions that occur during tawaf, ablution can be done before performing tawaf, while if in the middle of tawaf the ablution is invalidated because of touching the opposite sex when jostling, then it is permissible to take the opinion that ablution is not obligatory, as a form of convenience in Islam. The implication of this research is that it is expected to be a reference, literature and reference material for readers in the problem of fiqh of worship for the community in general and especially for those who will perform the hajj and umrah.